Autosomal recessive primary microcephaly due to ASPM mutations: An update. Issue 3 (16th January 2018) - Létard, Pascaline; Drunat, Séverine; Vial, Yoann; Duerinckx, Sarah; Ernault, Anais; Amram, Daniel; Arpin, Stéphanie; Bertoli, Marta; Busa, Tiffany; Ceulemans, Berten; Desir, Julie; Doco‐Fenzy, Martine; et al.
Abstract: Autosomal recessive microcephaly or microcephaly primary hereditary (MCPH) is a genetically heterogeneous neurodevelopmental disorder characterized by a reduction in brain volume, indirectly measured by an occipitofrontal circumference (OFC) 2 standard deviations or more below the age‐ and sex‐matched mean (−2SD) at birth and −3SD after 6 months, and leading to intellectual disability of variable severity. The abnormal spindle‐like microcephaly gene ( ASPM ), the human ortholog of the Drosophila melanogaster "abnormal spindle" gene ( asp ), encodes ASPM, a protein localized at the centrosome of apical neuroprogenitor cells and involved in spindle pole positioning during neurogenesis. Loss‐of‐function mutations in ASPM cause MCPH5, which affects the majority of all MCPH patients worldwide. Here, we report 47 unpublished patients from 39 families carrying 28 new ASPM mutations, and conduct an exhaustive review of the molecular, clinical, neuroradiological, and neuropsychological features of the 282 families previously reported (with 161 distinct ASPM mutations). Furthermore, we show that ASPM‐related microcephaly is not systematically associated with intellectual deficiency and discuss the association between the structural brain defects (strong reduction in cortical volume and surface area) that modify the cortical map of these patients and their cognitive abilities. Abstract : Loss‐of‐function mutations in the Abnormal SPindle‐like Microcephaly gene ( ASPM ) cause MicroCephaly Primary Hereditary (MCPH) type 5, defined by reduced brain volumes associated with intellectual disability. We compiled the molecular, clinical, neuroradiological and neuropsychological features of 47 patients (39 families, 28 novel mutations), and reviewed those of 282 previously reported families. We report that ASPM‐related microcephaly is not systematically associated with intellectual deficiency and discuss the association between structural brain defects (strongly reduced cortical volume and surface area) and cognitive abilities.